2017
DOI: 10.1111/jphd.12239
|View full text |Cite
|
Sign up to set email alerts
|

Basic income guarantee: a review of implications for oral health

Abstract: Our findings illustrate the importance of assessing oral health-related outcomes in future BIG pilot projects.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 49 publications
0
8
0
Order By: Relevance
“…So far, no empirical study examined the impact of a basic income on oral health. However, the existing evidence for impacts on health and socioeconomic outcomes suggests that a basic income could reduce the oral health inequalities caused by poverty and income inequality 59 . Pilot studies have shown that basic income guarantees are linked to better educational outcomes, better mental health, lower overall hospitalization rates, and healthier diets, all of which would likely have positive knock‐on effects on oral health.…”
Section: Direct Approaches To Reducing Fundamental Economic Inequalitymentioning
confidence: 99%
“…So far, no empirical study examined the impact of a basic income on oral health. However, the existing evidence for impacts on health and socioeconomic outcomes suggests that a basic income could reduce the oral health inequalities caused by poverty and income inequality 59 . Pilot studies have shown that basic income guarantees are linked to better educational outcomes, better mental health, lower overall hospitalization rates, and healthier diets, all of which would likely have positive knock‐on effects on oral health.…”
Section: Direct Approaches To Reducing Fundamental Economic Inequalitymentioning
confidence: 99%
“…The second type emphasizes the target population is receiving BI with a relatively more concrete sense. In this type, scholars usually assert that one with citizenship is qualified to be the recipient of BI (Von Gliszczynski 2017;Chen and Quinonez 2018;Van Parijs 1991). In some cases, being an adult is another requirement in a stricter case (Van der Veen 1998;McKay and Vanevery 2000;McKay 2001).…”
Section: Definition Of Bimentioning
confidence: 99%
“…The institution is the fourth most mentioned vital attribute in the BI definition, and it is relevant to who would be responsible for implementing BI. Twelve pieces of literature commonly describe a government or a political establishment takes the role (Bill 1988;Achterberg 2002;Cruz-Saco 2002;Van Parijs 2004;Raventós 2007;Lovett 2009;Krozer 2010;Zwolinski 2011;Beck et al 2015;Chen and Quinonez 2018;Pateman 2004;Davies and Bregman 2017). And the level of government is determined by the scale of BI.…”
Section: Definition Of Bimentioning
confidence: 99%
See 2 more Smart Citations